Screening immune adjuvants for an inactivated vaccine against Erysipelothrix rhusiopathiae - Guan, Li-Jun; Pei, Shi-Xuan; Song, Ji-Jian; Zhan, Peng-Fei; Han, Yi-Nong; Xue, Yun; Ding, Ke; Zhao, Zhan-Qin (Frontiers in Veterinary Science, 2022)
In this study, we screened adjuvants for an inactivated vaccine against Erysipelothrix rhusiopathiae (E. rhusiopathiae). Inactivated cells of E. rhusiopathiae strain HG-1 were prepared as the antigen in five adjuvanted inactivated vaccines, including a mineral-oil-adjuvanted vaccine (Oli vaccine), aluminum-hydroxide-gel-adjuvanted vaccine (Alh vaccine), ISA201-biphasic-oil-emulsion-adjuvanted vaccine (ISA201 vaccine), GEL02-water-soluble-polymer-adjuvanted vaccine (GEL vaccine), and IMS1313-water-soluble-nanoparticle-adjuvanted vaccine (IMS1313 vaccine). The safety test results of subcutaneous inoculation in mice showed that Oli vaccine had the most severe side effects, with a combined score of 35, followed by the ISA201 vaccine (25 points), Alh vaccine (20 points), GEL vaccine (10 points), and IMS1313 vaccine (10 points). A dose of 1.5LD50 of strain HG-1 was used to challenge the mice intraperitoneally, 14 days after their second immunization. The protective efficacy of Oli vaccine and Alh vaccine was 100% (8/8), whereas that of the other three adjuvanted vaccines was 88% (7/8). Challenge with 2.5LD50 of strain HG-1 resulted in a 100% survival rate, demonstrating the 100% protective efficacy of the Oli vaccine, followed by the GEL vaccine (71%, 5/7), IMS1313 vaccine (57%, 4/7), ISA201 vaccine (43%, 3/7), and Alh vaccine (29%, 2/7). Challenge with 4LD50 of strain HG-1 showed 100% (7/7) protective efficacy of the Oli vaccine and 71% (5/7) protective efficacy of the GEL vaccine, whereas the protective efficacy of other three adjuvanted vaccine was 14% (1/7). The Alh and GEL vaccines were selected for comparative tests in piglets, and both caused minor side effects. A second immunization with these two adjuvanted vaccines conferred 60% and 100% protective efficacy, respectively, after the piglets were challenged via an ear vein with 8LD100 of strain HG-1. After challenge with 16LD100 of strain HG-1, the Alh and GEL vaccines showed 40% and 100% protective efficacy, respectively. Our results suggested that GEL is the optimal adjuvant for an inactivated vaccine against E. rhusiopathiae.